A Long-Term Polydromic Function to Disentangle Personal Remittance, Migration and Employment in Agriculture in Order to Raise the GDP of the Donor aid Ratio in Five African Countries - Ebrima, K. Ceesay; Giorgio, Masoero (Journal of Agronomy Research, 2021)
Economic statistics concerning the quinquennial features of Agriculture employment (A), net Migration (M), Donor aid (D) and Personal remittances (P), available for over forty years from five West African countries have here been related to the GDP (G). The overall results of a multilinear regression (R2 0.84) have confirmed that the GD ratio, which is an index of aid efficiency, is significantly and positively driven by the PD ratio (high P and low D - favorable) and the PA ratio (high P and low A - favorable), but negatively driven by the PG ratio ( a higher D efficiency is obtained for constant G and lower P). A higher migration flux corresponds to a non-significant rise in the GD ratio. The five countries are clustered, by means of a principal component analysis, into three types. Partial least square regressions fitted to the GD ratio within each cluster provide a long-term polydromic function that highlights certain particular cluster features: reactive to forcing factors, such as Donor diminutions (SEN), active, as driven by Personal remittance (MLI), and mostly entropic for GMB, GNB and MRT. The learnt from the database is that Donor variations may follow different evolutions of the GD ratio in the three clusters.
Keywords: Agriculture employment; GDP-to-donor aid; Multilinear regression (MLR); Partial least squares regression (PLSR); Principal component analysis (PCA); West African countries